Pengaruh Kemiskinan, Pengangguran, Jumlah Penduduk Terhadap Pertumbuhan Ekonomi Kabupaten dan Kota di Jawa Timur Tahun 2015 – 2019 - Budi Prayitno; Renta Yustie (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2021)
Regional economic development has the main objectives, namely the prosperity of the region and the prosperity of the local community. Local governments and communities try to use and manage the resources in their area to the fullest. This study discusses the effects of poverty, unemployment, population on the economic growth of districts and cities in East Java in 2015-2019. The purpose of this study was to find out how the development of economic growth in districts and cities in East Java during 2015-2019. The method used in this study is panel data regression and statistical testing. This result are R2 is 0. 269270, F test with p-value is 0,0000 use alpha 0,05 and t-test variable poverty and unemployment are have significan 0.0000 and 0.0004 and t-test variable population not significan 0.1858